Diasporic Dances: Theological Musings Betwixt and Between Blackness - Edmonds, Joseph L. Tucker (Black theology, 2017)
This article brings Black theology into conversation with the diasporic character of Black identity, in addition to critical theorizing on late capital. By being attentive not only to the normative racializing strategy in the United States, but also attending to the persistence of colour-caste systems, the contemporary movement of global bodies and theories, and the impact of multiple performances of Blackness on racial identification, this article argues for a new theological method. This attempt to trouble Black race and the Black body, its use in theological scholarship, and to identify its descriptive and analytic deficiencies are facilitated by conversations with African theology, Critical Race Theory and Kelly Brown Douglas and Judith Bulter's theories on gender and performance. Finally, this article argues for a theology of diaspora that takes seriously the troubling of race, the reconsideration of embodiedness, and the excavation of difference and variety as a liberatory project.